2023
DOI: 10.1044/2022_jslhr-22-00003
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Communicative Intents Among 3- to 4.5-Year-Old French-Speaking Children: Procedure and Data From the Early Longitudinal Language and Neglect Study

Abstract: Purpose: This study aimed to (a) provide speech-language pathologists and researchers with a play-based procedure to measure the expression of spoken communicative intents by children aged 3 to 4.5 years and (b) present indicators of these children's capacity to produce these intents in this context. Method: A method inspired by TRIAGE (Technique de Recherche d'Informations par Animation d'un Group d'Experts) allowed an advisory group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Based on this, the experts confirmed that speech development work with these children should also be started from an early age. This means that children with profound mental retardation should also be encouraged to communicate verbally, but bearing in mind that any speech development training should be interested the child and encouraged him to interact with real objects and toys (Sante, & Leblond, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, the experts confirmed that speech development work with these children should also be started from an early age. This means that children with profound mental retardation should also be encouraged to communicate verbally, but bearing in mind that any speech development training should be interested the child and encouraged him to interact with real objects and toys (Sante, & Leblond, 2023).…”
Section: Resultsmentioning
confidence: 99%